Working animals' rights: A disruption to the status quo. (June 2017) - Shaw, Rosemary
This article presents a thought project on how the law ought to treat working animals. The author argues that work health and safety legislation needs to take a fresh, contemporary and inclusive approach which challenges our anthropocentric mentality and recognises those animals that contribute to our economy through work. A critical reading of key sections of Australia's model work health and safety legislation, as a representative example of contemporary work health and safety law, supports the contention working animals should be included as 'workers' under such laws.